Endoscopic ultrasound-guided gastroenterostomy (gastroenteric anastomosis) - Joel Fernandez de Oliveira; Matheus Cavalcante Franco; Gustavo Rodela; Fauze Maluf-Filho; Bruno Costa Martins (Society of Gastrointestinal Intervention, 2022)
Endoscopic ultrasound-guided gastroenterostomy (EUS-GE) has emerged as a promising minimally invasive technique for patients with gastric outlet obstruction (GOO), regardless of whether a benign or malignant condition impedes gastric emptying. EUS-GE involves creating a bypass from the stomach to the small bowel distally to the obstruction, which is similar to the surgical gastroenteric anastomosis. In fact, EUS-GE has been reported to have longer stent patency in patients with malignant GOO than conventional self-expandable metal stents deployed across a malignant obstruction. Although surgical treatment is still considered the gold-standard treatment for patients with malignant GOO, the results of recent studies have shown not only similar rates of technical and clinical success with EUS-GE, but also lower rates of adverse events. In this review, we aimed to appraise the current status of EUS-GE, describe the multiple techniques to perform this procedure, compare the outcomes of EUS-GE with those of other therapeutic modalities, and discuss the related adverse events and the future perspectives of EUS-GE.